BBQE: multi-language string search approach for blackberry environment - Mantoro, Teddy; Ayu, Media Anugerah; Mercic, Merdin (2011)
Mobile application development seems in popularity in a very fast pace. The reason for this is that pervasive computing and applications related to it, share small, inexpensive and robust networked processing devices distributed at all scales throughout everyday life. This paper discussed on how wireless networks affect the performance of a multi-language string search client-server based application for a Blackberry device in comparison to a standalone application. As a case study, five Al-Quran translations are used as proof of concept that string-search can be implemented in an efficient and fast search manner in several databases. The performance comparison between standalone and client-server application is presented including the discussion of the BBQE prototype.